FOREIGN FIGHTERS AND THE EXTREME RIGHT tracking far-right volunteers beyond. (ROUTLEDGE, 2026)
Foreign Fighters and the Extreme Right is the first comprehensive academic study taking an in-depth look at white supremacists, neo-Nazis and other right-wing extremists leaving their home countries to join armed groups fighting in civil wars and other armed conflicts.The phenomenon known as 'Foreign Fighters' has so far mainly been looked at in the context of Jihadist groups like ISIS recruiting fighters from all over the world for the Syrian and Iraqi conflicts. Widely unnoticed, the war ongoing in Ukraine has also resulted in a stream of foreign recruits but with a totally different ideology. Right-wing extremists from many countries have travelled to Ukraine in order to take part in the armed conflict against Russia. Many have already returned to their countries of origin, mostly unnoticed and unhindered by law enforcement agencies. Looking more carefully, one also can see a much longer history of right-wing extremist foreign fighting in various conflicts, for example, the Yugoslavian war, the Algerian conflict and in South America in the aftermath of the Vietnam war. Bringing together world- leading experts on right- wing extremism and terrorism, this collection of extreme right-wing foreign fighting case studies since the end of the Second World War sheds light on a topic with significant importance, which has yet remained mostly in the dark.This book will be of interest to all those with an interest in small wars, terrorism, peace and conflict studies and right-wing extremism.
Keywords: Russian Invasion of Ukraine, 2022.; Military service, Voluntary -- Ukraine -- History -- 21st century.; Volunteers -- Ukraine -- History -- 21st century.; Soldiers -- Ukraine -- Interviews.; elektronické knihy; electronic books